Amazing human body - Cohen, Andrew (Scientist); Paterson, Nigel; Heron, Zoe; Hayes, Michael J. (Voice actor); Johnson, Martin (Documentary film director); Dyas, Matthew; Palmer, Penny; BBC Studios; Public Broadcasting Service (U.S.); British Broadcasting Corporation; PBS Distribution (Firm) ([Arlington, Virginia] : PBS, 2018)
This three-part series uses cutting-edge graphics to reveal the surprisingly beautiful biological processes that keep one alive. Discover the ingenious ways your body develops, adapts, and endures, and witness the fascinating and finely tuned systems that keep one's body motoring, and the scientists guessing.
episode 1. Grow / produced and directed by Martin Johnson -- episode 2. Survive / produced and directed by Matthew Dyas -- episode 3. Learn / produced and directed by Penny Palmer.
Title from disc surface.
Narrator, Michael J. Hayes.
Grade: Middle school (6-8).
TV-PG.
DVD; Widescreen (16x9) presentation; Stereo; Region 1.
In English with optional English subtitles for the deaf and hard-of-hearing (SDH).
Keywords: Human body; Human physiology; Human anatomy; Video recordings for the hearing impaired; Science television programs; Nonfiction television programs; DVD-Video discs; Educational television programs; Documentary television programs